KEPASTIAN HUKUM TERHADAP HAK-HAK MANTAN ISTERI PASCA PERCERAIAN (STUDI KASUS PUTUSAN PENGADILAN AGAMA JAKARTA UTARA NOMOR: 299/PDT.G/2021/PA.JU) - Aji Ulul Azmi; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2021)
The fulfillment of a wife's livelihood does not only apply in marriage, but also after divorce. The problem is that there are often many divorce cases where the rights of ex-wives (iddah and mut'ah) are not fulfilled even though the decision requires them to be paid. This is like what happened in the North Jakarta Religious Court Decision Case Number: 299/Pdt.G/2021/Pa.Ju, so the problem arises how is the legal certainty of the rights of an ex-wife after divorce to the rights of iddah and mut'ah money? and what are the legal remedies if the iddah and mut'ah payments are not carried out in accordance with the North Jakarta Court Decision Number: 299/PDT.G/2020/PA.JU?Based on the analytical study that the ruling in the divorce case in the North Jakarta Religious Court Decision Number 299/PDT.G/2021/PA.JU regarding the rights of the wife after the divorce to the rights of iddah and mut'ah money, has not provided legal certainty, especially in certainty of execution of the judge's decision. This is because the ruling that requires the ex-husband to pay the iddah and mut'ah money has not been received before the divorce pledge is made, causing legal uncertainty, especially for divorced wives. Legal remedies that can be taken by the ex-wife if the iddah and mut'ah payments are not carried out according to the court's decision the means that can be done is to apply for execution at the religious court.